2016
DOI: 10.3109/00016489.2016.1157265
|View full text |Cite
|
Sign up to set email alerts
|

Association of the microsatellite (GT)n repeat polymorphisms of the HO-1 gene promoter and corresponding serum levels with the risk of laryngeal squamous cell carcinoma

Abstract: Compared with the controls, the LSCC group had significantly higher frequencies of L-allele (> 29 repeats) and L-allele carriers (p < 0.001, OR = 2.037 and p = 0.005, OR = 2.152, respectively). The frequencies of lymph node metastasis and of moderate or poor differentiation were significantly higher in L-allele carriers compared to non-L-allele carriers (p < 0.05). Significantly lower serum HO-1 levels were detected in LSCC patients (p < 0.001), and patients with lower serum HO-1 levels had more advanced cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…On the other hand, the long (GT)n repeats in HMOX1 gene promoter was reported to correlate with a higher risk of breast cancer [ 54 ], esophageal squamous cell carcinoma [ 55 ] and laryngeal squamous cell carcinoma [ 56 ]. More complicated, other studies showed no correlation between HMOX1 polymorphism and the risk of lung squamous cell carcinoma [ 57 ] and sporadic colorectal cancer [ 58 ], indicating that the final outcome may depend on several factors including the type of the tumor, subject ethnicity, and many others.…”
Section: Association Between Ho-1 Gene Polymorphism and Cancermentioning
confidence: 99%
“…On the other hand, the long (GT)n repeats in HMOX1 gene promoter was reported to correlate with a higher risk of breast cancer [ 54 ], esophageal squamous cell carcinoma [ 55 ] and laryngeal squamous cell carcinoma [ 56 ]. More complicated, other studies showed no correlation between HMOX1 polymorphism and the risk of lung squamous cell carcinoma [ 57 ] and sporadic colorectal cancer [ 58 ], indicating that the final outcome may depend on several factors including the type of the tumor, subject ethnicity, and many others.…”
Section: Association Between Ho-1 Gene Polymorphism and Cancermentioning
confidence: 99%
“…The titles and abstracts were reviewed considering the inclusion and exclusion criteria. Finally, 5 articles were considered eligible for this systematic review: Zhou et al ( 23 ), Zhou et al ( 17 ), Tang et al ( 16 ), Zhou et al ( 6 ), and Yang et al ( 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have found a significant positive association between molecular markers and VFL ( 6 , 16 ), but some researchers did not find a genetic association ( 5 , 17 ). Besides, the lack of review studies on this topic emphasizes the need for evidence synthesis to better understand the genetics in VFL etiology.…”
Section: Introductionmentioning
confidence: 99%
“…in pediatric patients with acute lymphoblastic leukemia, patients with Ho-1 S (GT) n repeats were associated with chemotherapy resistance and chemo-induced neutropenia (92). in other studies, l (GT)n repeats in the promoter of the Ho-1 gene have been reported to be associated with a higher risk of breast cancer, esophageal squamous cell carcinoma and laryngeal squamous cell carcinoma (67,(93)(94)(95).…”
Section: Association Between Ho-1 Gene Polymorphism and Clinical Diseasesmentioning
confidence: 92%